Additive influence of hip offset and leg length reconstruction on postoperative improvement in clinical outcome after total hip arthroplasty - Innmann, Moritz Maximilian; Maier, Michael Wolfgang; Streit, Marcus R.; Bruckner, Thomas; Gotterbarm, Tobias; Merle, Christian (The journal of arthroplasty, 2018)
Background: There is a lack of prospective studies investigating the additive effect of both acetabular and femoral reconstruction parameters on the functional outcome following total hip arthroplasty (THA). Methods: The aim of this prospective cohort study was to determine the combined influence of hip geometry reconstruction and component positioning on the clinical outcome following primary THA for unilateral osteoarthritis. We prospectively assessed the clinical outcome and radiographic parameters for hip geometry reconstruction, component position, and orientation using validated measurements for the operated hip compared to the contralateral native hip in a consecutive series of 113 patients with primary unilateral cementless THA. The correlation of reconstruction parameters was investigated using a multivariate polynomial regression model for the dependent variable ΔHHS (difference between the Harris hip scores preoperatively and 2.0-4.8 years postoperatively). Target zones for hip reconstruction and component positioning were investigated for an association with superior clinical outcome. Results: The regression model demonstrated a significant correlation for the ΔHHS and both hip offset (HO) reconstruction and leg length difference. Patients with accurate to slightly increased HO reconstruction combined with balanced leg length demonstrated a significantly higher ΔHHS than patients outside this zone (HO: 5 ± 5 and LLD: 0 ±5 mm, P = .029). This finding could be confirmed for 2 enlarged zones (zone 1: HO, 7.5 ± 7.5 and LLD, 2.5 ± 7.5 mm, P = .028; zone 2: HO, 7.5 ± 7.5 and LLD, 7.5 ± 7.5 mm, P = .007). Conclusion HO and leg length reconstruction demonstrated an additive effect on clinical outcome and surgeons should aim for high accuracy in the reconstruction of both factors.
Online 12 August 2017
Gesehen am 20.11.2018